The vanishing boundaries between technical and political: normativism and pragmatism in the Brazilian courts’ adjustment of public policies - Fonseca, Juliana Pondé (Revista de Investigações Constitucionais, 2015)
In law, normativism and pragmatism have always been under tension and this has been revealed in many different ways. One of its manifestations can be found in adjudication, where the technical/juridical role of the judge has, in many countries, assumed political contours, a phenomenon described as “judicialization of politics”. This paper will examine the vanishing boundaries between the technical and the political, using Brazil as an example, and will analyze the hypothesis that the existence of clear borderlines, in these terms, is thing of the past. The formalist assumption that judges only subsume facts into abstract rules has been ruled out by most scholars, but the institutional design and the concept of separation of powers that come with it have not. The investigation of the courts’ current practices and the consideration of legal theory show that these limits should be redesigned.